Study of the bacteriostatic activity of an Artemia enrichment compound based on plant extracts from Angelica sp. - ATHANASSOPOULOU (Φ. ΑΘΑΝΑΣΟΠΟΥΛΟΥ) F.; KOTOU, E.; WATSOS (Ε. ΒΑΤΣΟΣ) E.; GIAGNISI (Μ. ΓΙΑΓΝΙΣΗ) M. (Journal of the Hellenic Veterinary Medical Society, 2018)
The bacteriostatic ability of a commercial product was assessed against Vibrio alginolyticus and V anguillarum at concentations 1,3,4,6.5 and 15ppm. The best concentration for short term (48hrs) arrestment of the nonpathogenic bacteria was found l-3ppm whereas for longer effect (72hrs) the best concentration for both species was 6,5ppm. Higher concentrations did not show any advantages.